Green energy powered - vapor, thermal and UV light assisted disinfection technology - Kishor Kumar Sadasivuni (1389276) (2023)
Infectious diseases are responsible for an immense global burden of disease that impacts public health systems and economies worldwide. The rapid increase in the use of protective items has introduced an urge for their reuse and safe dumping to minimize the threat of disease transmission through cross-contamination. The existing disinfection processes are mostly powered with non-renewable energy sources and focus on single disinfecting technology that limits their installation to in-house applications and reduces the degree of disinfection, respectively. Thus there is a need to develop new strategies and innovations powered by renewable energy sources that enhance the degree of disinfection of daily-use objects and curtail the spread of the infection through cross-contamination. The present study reports a smart automatic technology called “REACTIV-FIT”. The technology is developed as an exercise bike with a disinfection chamber that efficiently kills viruses, bacteria, and other germs/pathogens. The current developed technology is equipped with three disinfecting protocols in one system. The system is powered by renewable solar energy and utilizes the mechanical energy during exercise into electrical energy using a generator-based mechanism. The portable smart automatic disinfection box embedded in the bike utilizes the synergetic effect of ultraviolet (UV), thermal, and vapor treatment for sterilizing objects. During vapor treatment, the continuous supply of the sterilizing solution is maintained through a storage tank attached to the outer body of the box and can be easily refilled. In the final step of the disinfecting protocol, the objects are exposed to UV-A light having a peak wavelength of 365–370 nm. The automatic disinfection process is powered by renewable solar and mechanical energy during cycling. The developed technology can be installed in schools, offices, and industries, and its renewable energy-powered feature offers installation in parks, tourist places, streets, remote areas, etc. Other Information Published in: Materials Today: Proceedings License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.matpr.2023.02.245